GAMBARAN FAKTOR-FAKTOR YANG MEMENGARUHI TUMBUH KEMBANG BALITA YANG TINGGAL DI SEKITAR TPA BLONDO-BAWEN, KABUPATEN SEMARANG - Puspita, Dhanang; ., Dary; Suwarso, Etika Noviyanti (KRITIS, 2018)
This research is motivated by factors that affect the growth and development of toddlers in final disposal sites (TPA), namely those related to nutritional status, chronic disease or infection, health care, environmental sanitation. The research objective was to determine the factors that influence the growth and development of children under five who live around TPA Blondo, Bawen, Semarang Regency. This research used quantitative descriptive method with univariate analysis data processing. The study population was probably 30 toddlers 1 - 5 years old with a total sampling technique of 30 toddlers. Results of the study: 22 toddlers (73.33%) with good nutritional status and 8 under-fives (26.67%) of malnutrition. There were 21 children under five (70%) who had suffered chronic disease and 9 children under five (30%) never had chronic disease. There were 27 toddlers in an environment that had adequate sanitation status (90%) and 3 under-fives (10%) who were in an environment with insufficient sanitation status. Health care with sufficient criteria as many as 26 toddlers (86.67%) and less criteria as many as 4 children under five (13.33%). Factors affecting growth and development; lack of nutrition, food intake for toddlers is not balanced.